Treatment of facial lipoatrophy in people infected by HIV/AIDS: moving away from prejudice and improving quality of life - Andréia Campos Matos; Rafaela Scotto Boletini; Thalitta Cristina Keating; Norma Fumie Matsumoto; Maria Ângela Gandolpho (O Mundo da Saúde, 2010)
Nowadays we observe a higher control of AIDS, with the advent of anti-retroviral therapies, although people infected by HIV continue susceptible to a series of physical, psychological and social consequences. One of them is face lipoatrophy, caused by anti-retroviral treatments, which cause intense modifications in the face. A treatment considered and made available by SUS (Brazil’s Unified Health System), polymetilmetacrilate for skin filling. This article is the result of a research aiming at knowing how people infected by HIV/AIDS feel regarding facial lipoatrophy and the meaning of having skin filling. The study was developed through a qualitative methodology, with an intentional sample of eight individuals submitted to the skin filling treatment. Data treatment was carried through the Collective Subject Discourse and results had two important moments. The first is related to the presence of facial lipoatrophy, where central ideas demonstrate the reduction of self-esteem, non satisfaction with self-image, and fears and problems generated by stigmata and discrimination against HIV/AIDS. On the other hand this negative feeling about skin filling becomes an important and positive landmark with the return of self-esteem and improvements of self-image and adhesion to treatment. We could conclude that free treatment of facial lipoatrophy increased the quality of life of subjects, improving their “distorted” appearance, helping them to rescue their identity and dignity, preserving them from discrimination and prejudice.